Pengelompokan dan Struktur Populasi Parasitoid Telur Trichogrammatoidea armigera pada Telur Helicoverpa armigera pada Jagung Berdasarkan Karakter Molekuler - BAHAGIAWATI AMIR HUSIN; DWINITA W UTAMI; DAMAYANTI BUCHORI (Jurnal Entomologi Indonesia, 2010)
The effectiveness of this parasitoid was influenced by its population structure in the field. However, because this parasitoid has a tiny size, it was difficult to know the population structure of this parasitoid. This problem can be overcome by using molecular characteristic i.e. molecular markers. Based on RAPD-PCR analysis from 4 selected primers on 19 DNA samples from 3 different locations it was fond, that Gunung Bunder II population was divided into sub-population and so did Cugenang population, which is indicated by their small Fst and Nm index. The Fst and Nm index for Gunung Bunder II population was 0,39 and 0,77, while 0,51 and 0,47 for Cugenang population. If we calculated the Fst and Nm for all samples together, we found that this parasitoid has a random mating pattern, which is also shown by the dendrogram. The dendrogram indicate that each sub- opulation from one location was not grouped in one cluster but distributed in every cluster.